2007
DOI: 10.1111/j.1468-3148.2006.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents Plus Programme 1: Evaluation of Its Effectiveness for Pre‐School Children with Developmental Disabilities and Behavioural Problems

Abstract: Background  This study aimed to evaluate the effectiveness of the Parents Plus programme with families of pre‐school children with developmental disabilities and significant behavioural problems in the Irish health service. The Parents Plus programme is a group‐based parent training package involving video modelling, which was designed to be effective for children with conduct problems, but without developmental disabilities. Materials and methods  Pre‐ and post‐treatment assessments were conducted with 22 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
3
33
1
Order By: Relevance
“…those measured weeks or months following treatment end) were not analyzed in this meta-analysis. Quinn et al (2007) evaluated child behavior using both the CBCL and the SDQ. In this case the effect sizes were standardized and averaged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…those measured weeks or months following treatment end) were not analyzed in this meta-analysis. Quinn et al (2007) evaluated child behavior using both the CBCL and the SDQ. In this case the effect sizes were standardized and averaged.…”
Section: Discussionmentioning
confidence: 99%
“…The Parents' Plus Programmes are evidence-based programs delivered in small groups and use a videobased format to illustrate both negative and positive family interactions. The sessions also include group discussions and assigned homework (Quinn et al, 2007). Two types of Parents Plus Programmes evaluated in this meta-analysis -Children's Programme (Coughlin et al, 2009;Quinn et al, 2007) for children ages 6-12 years of age, and a modified version of the Children's Programme, adapted to accommodate children with a developmental disability, examined by Hand, Raghallaigh, et al (2013).…”
Section: Types Of Pmtmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown that the Parents Plus Programs are effective in reducing childhood behavior problems and associated parental stress in clinical settings for a variety of age groups (e.g., Behan, Fitzpatrick, Sharry, Carr, & Waldron, 2001;Coughlin, Sharry, Fitzpatrick, Guerin, & Drumm, 2009;Quinn, Carr, Carroll, & O'Sullivan, 2007). In particular, the PPEY Program has been shown to reduce conduct problems, hyperactivity, and parental stress and to help parents move significantly closer to their goals when conducted in a clinical setting by mental health professionals (Griffin, Guerin, Sharry, & Drumm, 2010); however, many parents display limited attendance with clinic-based programs and are less likely to complete treatment (Kazdin, Mazurick, & Bass, 1993), with some parents reporting feeling stigma attached to attending child and adolescent mental health services (Bradby et al, 2007).…”
Section: Parents Plus Programmentioning
confidence: 99%